U.S.-Japan relations in the era of Trump: Navigating the turbulence of “America First” - Solís, Mireya (México y la Cuenca del Pacífico, 2019)
Guest Opinion of U.S.-Japan relations in the era of Trump: Navigating the turbulence of “America First”